The Effect of Silica Particle Sizes and Promoters to Equilibrium Moisture Content for CO2 Hydrate Formation in HPVA - Abu Hassan, MH; Snape, CE; Steven, L (Amer Inst Physics, 2024)
The formation of CO2 hydrate (CO2:6H(2)O) in this work was experimentally investigated in batch mode inside a high pressure volumetric analyser (HPVA). The investigations in pure CO2 gas systems highlighted the effect of type of silicas used and the concentration of promoters used on the amount of equilibrium moisture content available for formation of hydrate. Standard silica gel was the only silica found to show hydrate formation due to the best distribution of pore size with the amount of equilibrium moisture content of 14.8 wt%. The high amount of bulk water inside zeolites 13X and spherical MCF-17 (21.3 and 50.8 wt% respectively) was the main reason of no hydrate formation observed due to the interstitial spaces between both silica particles were fully occupied by water. In other words, diffusion of gas molecules into the water is required for hydrate nucleation as well as hydrate growth. Additionally, the combined-promoters designated type T1-5 (0.01 mol% sodium dodecyl sulphate (SDS) + 5.6 mol% tetrahydrofuran (THF)) was the best obtaining a CO2 uptake of 5.95 mmol of CO2 per g of H2O with the amount of equilibrium moisture content of 13.28 wt%.